Design and Implementation of a COVID-19 Case Investigation Program: An Academic–Public Health Partnership, Arizona, 2020. (March 2022) - Ledesma, Daniela; Maroofi, Hanna; Sabin, Susanna; Dennehy, Timothy J.; Truong, Jasmine M.; Meyer, Laura G.; Salik, McMillan; Scott, Sarah; White, Jessica R.; Collins, Jennifer; Mrukowicz, Christina; Charifson, Mia; et al.
From May through July 2020, Arizona was a global hotspot for new COVID-19 cases. In response to the surge of cases, local public health departments looked for innovative ways to form external partnerships to address their staffing needs. In collaboration with the Maricopa County Department of Public Health, the Arizona State University Student Outbreak Response Team (SORT) created and implemented a virtual call center to conduct public health case investigations for COVID-19. SORT officially launched a dedicated COVID-19 case investigation program after 3 weeks of program design and training. From June 29 through November 8, 2020, SORT recruited and trained 218 case investigators, completed 5000 case patient interviews, and closed 10 000 cases. Our team also developed process improvements to address disparities in case investigation timeliness. A strong infrastructure designed to accommodate remote case investigations, paired with a large workforce, enabled SORT to provide additional surge capacity for the county's high volume of cases. University-driven multidisciplinary case investigator teams working in partnership with state, tribal, and local public health staff members can be an effective tool for supporting a diverse and growing public health workforce. We discuss the essential design factors involved in building a university program to complement local COVID-19 response efforts, including workflows for case management, volunteer case investigator recruitment and training, secure technology platforms for conducting case investigations remotely, and robust data-tracking procedures for maintaining quality control and timely case reporting.